Institutional characteristics of education systems and inequalities: Introduction II. (April 2022) - Gross, Christiane; Hadjar, Andreas; Zapfe, Laura
The second special issue of International Journal of Comparative Sociology (IJCS) on the role of education systems as institutional settings on the reproduction of inequalities includes three papers that focus on stratification of the education system as key driver of educational inequalities, the role of digital inequalities in the school and beyond, as well as how students navigate through the institutional setting of the Taiwanese education system. While we already elaborated on the research program, conceptual framework, and methodological challenges in the first introduction (published in January 2021), we will deal with the current state-of-research in this second introduction.